Heat Exchanger Analysis to Reduce Hexane Loss in Palm Kernel Oil Extraction Plant - Sivarao, Subramonian; Nantha, kumar; Taufik; Sivakumar, Dhar Malingam; Mohd Amri , Sulaiman; Kassim, M.S (IJENS Publishers, 2013)
The aim of this study is to reduce hexane loss during the process of extraction oil from palm kernel that would reduce the production cost and increase the net profit. The study is carried out in a leading palm oil factory in Malaysia. At present solvent extraction plant are facing problem of high hexane loss, average 9.5 litre/metric ton (ltr/mt). To reduce the hexane loss, critical investigations were performed to improve the heat transfer between hexane vapour and water condenser shell and tube. Preliminary investigations reveal that 21% of the hexane is being loss during plant operation. The present redesigned heat exchanger is successfully reduced the hexane loss from 9.5% ltr/mt to 7.5ltr/mt per day of the same operating plant which saves about RM904, 800 per annum for the industry. Ultimately, the outcome of this study gives a great economic impact to the industry by reducing the production cost leading into the reduction of oil price for the nation. In addition it is found that not only the monetary impact is benefited, but, the release of hexane to atmospheric also reduced to ensure safe healthy life of people surrounding the plant.